Myokines as Possible Therapeutic Targets in Cancer Cachexia - Emilia Manole; Laura C. Ceafalan; Bogdan O. Popescu; Carmen Dumitru; Alexandra E. Bastian (Journal of Immunology Research)
Cachexia is an extremely serious syndrome which occurs in most patients with different cancers, and it is characterized by systemic inflammation, a negative protein and energy balance, and involuntary loss of body mass. This syndrome has a dramatic impact on the patient’s quality of life, and it is also associated with a low response to chemotherapy leading to a decrease in survival. Despite this, cachexia is still underestimated and often untreated. New research is needed in this area to understand this complex phenomenon and ultimately find treatment methods and therapeutic targets. The skeletal muscle can act as an endocrine organ. Signaling between muscles and other systems is done through myokines, cytokines, and proteins produced and released by myocytes. In this review, we would like to draw attention to some of the most important myokines that could have potential as biomarkers and therapeutic targets: myostatin, irisin, myonectin, decorin, fibroblast growth factor 21, interleukin-6, interleukin-8, and interleukin-15.